Shorted operators and minus order - Contino, Maximiliano (2019)
Let H be a Hilbert space, L(H) the algebra of bounded linear operators on H and W ∈ L(H) a positive operator. Given a closed subspace S of H, we characterize the shorted operator W/S of W to S as the maximum and as the infimum of certain sets, for the minus order − ≤. Also, given A ∈ L(H) with closed range, we study the following operator approximation problem considering the minus order: min− ≤ {(AX − I) ∗W(AX − I) : X ∈ L(H), subject to N(A ∗W) ⊆ N(X)}. We show that, under certain conditions, the shorted operator of W/R(A) is the minimum of this problem and we characterize the set of solutions.